A Relativistic Jet in the Radio-quiet Active Galactic Nucleus Mrk 110 - Ailing Wang; Tao An; Kenneth I. Kellermann; Hua Feng; Emmanuel K. Bempong-Manful; Roland Timmerman; Shaoguang Guo (The Astrophysical Journal Letters, 2025)
We report the discovery of a relativistic jet in Mrk 110, a narrow-line Seyfert 1 galaxy historically classified as a radio-quiet active galactic nucleus (AGN). Very long baseline interferometry observations reveal intermittent jet activity during 2015–2016 and 2022–2024, with proper-motion measurements yielding superluminal velocities of ∼3.6 ± 0.6 c and ∼2.1 ± 0.2 c , respectively. The recent jet component decelerates to ∼1.5 ± 0.2 c at a projected distance of 1.1 pc from the core, coinciding with the transition zone between broad-line and narrow-line regions. This deceleration accompanies dramatic spectral evolution from steep (spectral index α  ≈ −0.63 ± 0.04) to inverted ( α  ≈ +0.69 ± 0.10) as the 7.6 GHz flux density more than doubled. These episodic jet ejections and their evolutionary pattern match theoretical predictions from magnetically arrested disk (MAD) models for temporary jet formation in systems with Mrk 110’s physical parameters on timescales of months to years. The observed jet deceleration distance matches expectations for relativistic outflows interacting with the circumnuclear environment. These findings demonstrate that the traditional radio-loud/quiet AGN dichotomy may reflect time-averaged states rather than intrinsic capabilities, suggesting that jets may form across the AGN population but become observable only during specific accretion phases when MAD conditions are temporarily established. Mrk 110 serves as a critical “missing link” between radio-loud and radio-quiet AGN, providing insight into jet formation mechanisms, environmental interactions, and physical processes that unify various AGN classifications.